2015
DOI: 10.1021/ja5103663
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Highly Stable Amorphous Zinc Phosphate Intermediates during the Formation of Zinc Phosphate Hydrate

Abstract: The mechanisms by which amorphous intermediates transform into crystalline materials are still poorly understood. Here we attempt to illuminate the formation of an amorphous precursor by investigating the crystallization process of zinc phosphate hydrate. This work shows that amorphous zinc phosphate (AZP) nanoparticles precipitate from aqueous solutions prior to the crystalline hopeite phase at low concentrations and in the absence of additives at room temperature. AZP nanoparticles are thermally stable again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 96 publications
5
36
0
Order By: Relevance
“…However, the presence of a low‐molecular organic compound (diethylene glycol) in the structure are thought to be responsible for the observed delay in crystallization. Similarly, in an elaborate study by Bach et al, the presence of non‐crystalline zinc phosphate nanoparticles as intermediate species, during the formation of crystalline zinc phosphate hydrates, was confirmed . This is consistent with the observed delay, of more than 24 hours, for the appearance of Bragg reflections in a BSA‐templated synthesis of zinc phosphate nanocomposites, as reported by Song et al Therefore, we speculate that the particles observed in sample C initially consist of a non‐crystalline zinc phosphate and, similar to that reported by Roming et al, exhibit a significant delay in crystallization due to organic components of the artificial saliva.…”
Section: Discussionsupporting
confidence: 91%
“…However, the presence of a low‐molecular organic compound (diethylene glycol) in the structure are thought to be responsible for the observed delay in crystallization. Similarly, in an elaborate study by Bach et al, the presence of non‐crystalline zinc phosphate nanoparticles as intermediate species, during the formation of crystalline zinc phosphate hydrates, was confirmed . This is consistent with the observed delay, of more than 24 hours, for the appearance of Bragg reflections in a BSA‐templated synthesis of zinc phosphate nanocomposites, as reported by Song et al Therefore, we speculate that the particles observed in sample C initially consist of a non‐crystalline zinc phosphate and, similar to that reported by Roming et al, exhibit a significant delay in crystallization due to organic components of the artificial saliva.…”
Section: Discussionsupporting
confidence: 91%
“…The X-ray diffraction (Figure S5) pattern is in accordance with the result obtained by Bach et al (2015). 32 Reference compounds were diluted in polyvinylpyrrolidone powder, ground and pressed into pellets for EXAFS analysis.…”
Section: Preparation Of Samples and Reference Compounds For Exafs Anamentioning
confidence: 99%
“…Solid-state NMR revealed water to occur as a molecular entity with little evidence for proton exchange, but with a reorientation on a time scale of milliseconds. 26 (ii) Configuration: The formation and configuration of the amorphous phase are difficult to unravel. An appealing formation model of a hydrated amorphous phase is the agglomeration of small cluster nuclei with solvation water molecules trapped by hydrogen bonding in between.…”
mentioning
confidence: 99%